IDENTITY AND ETHNICITY OF BUGIS COMMUNITY IN BALI: AN HISTORICAL PERSPECTIVE (History Department, Semarang State University and Historian Society of Indonesia, 2017)
This study aims to reveal the phenomenon of identity change of the Bugis people in Bali. Bugis community in a long period of time has experienced a variety of hegemony and marginalization, both in politics and economy. This study aims to find out how the construct-ion of identity and the struggle to face these challenges. The method used in this research was historical method combined with cultural studies. The data were collected through lite-rature materials combined with in-depth interviews. The results show that the change and identity politics carried out were a reaction to the hegemony and marginalization that they have experienced over the years, mainly due to external factors. The external factors include political factors (government policy) and economic factor, especially tourism. Penelitian ini bertujuan untuk mengungkapkan fenomena perubahan Identitas Masyarakat Bugis di Bali. Masyarakat Bugis dalam periode yang panjang mengalami berbagai hegemoni dan keterpinggiran, baik dalam bidang politik maupun ekonomi. Kajian ini ingin mengetahui bagaimana konstruksi identitas dan perjuangan menghadapi tantangan tersebut. Metode yang dipergunakan dalam penelitian ini adalah metode sejarah dan dikombinasikan dengan kajian budaya (culture studies). Data dikumpulkan lewat bahan-bahan kepustakaan dan dikombinasikan dengan wawancara mendalam. Hasil penelitian menunjukkan bahwa perubahan dan politik identitas yang dilakukan merupakan reaksi dari hegemoni dan marginalisasi yang mereka alami selama ini, terutama karena faktor eksternal. Faktor eksternal seperti faktor politik (kebijakan pemerintah) dan faktor ekonomi, terutama pariwisata.